Training Neural Networks Based on PSO Algorithm and BP Algorithm - Gao, Darong (2025 IEEE 5th International Conference on Power, Electronics and Computer Applications (ICPECA), 2025)
Signal processing has made extensive use of neural networks. This study examines neural network training using the PSO and BP algorithms. To train the neural network, the PSO algorithm alone, the BP algorithm alone, and the PSO algorithm combined with BP algorithm are examined for the same signal. It is determined that the PSO algorithm in conjunction with the BP algorithm can enhance the network's learning efficiency and accelerate its convergence.